2014
DOI: 10.1103/physrevb.90.045119
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cation arrangement on the electronic structures of the perovskite solid solutions <span class="aps-inline-formula"><math xmlns="http://www.w3.org/1998/Math/MathML"><msub><mrow><mo>(</mo><mi>SrTiO</mi></mrow><mn>3</mn></msub><mo>)</mo><msub><mrow></mrow><mrow><mn>1</mn><mo>−</mo><mi>x</mi></mrow></msub><msub><mrow><mo>(</mo

Abstract: The electronic structures of [SrTiO 3 ] 1−x [LaCrO 3 ] x perovskite solid solutions are studied using hybrid density functional calculations to investigate their potential photocatalytic activity. The introduction of Cr 3+ into SrTiO 3 not only creates occupied states inside the band gap but can adversely narrow the conduction band. However, if Cr 3+ and Ti 4+ ions are segregated in alternating [001] layers, the conduction band remains highly dispersive. This suggests that the electronic structure can be tuned… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
3
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 46 publications
1
3
0
Order By: Relevance
“…This behavior has been predicted theoretically using a density functional theory model of the SLTCO system for various doping levels, which showed that the density of states at the bottom of the conduction band was reduced. 24 The measured increase in the gap is qualitatively similar to the Burstein-Moss effect that occurs due to band filling of low-lying conduction band states, 25 which has been observed previously in La-doped STO. 26 However, we believe that a change in the conduction band density of states better explains the observations for two reasons: (1) the films are highly insulating; and (2) there is no evidence of a lowenergy Drude peak in the ellipsometry data, suggesting the absence of free carriers in the conduction band.…”
supporting
confidence: 82%
See 1 more Smart Citation
“…This behavior has been predicted theoretically using a density functional theory model of the SLTCO system for various doping levels, which showed that the density of states at the bottom of the conduction band was reduced. 24 The measured increase in the gap is qualitatively similar to the Burstein-Moss effect that occurs due to band filling of low-lying conduction band states, 25 which has been observed previously in La-doped STO. 26 However, we believe that a change in the conduction band density of states better explains the observations for two reasons: (1) the films are highly insulating; and (2) there is no evidence of a lowenergy Drude peak in the ellipsometry data, suggesting the absence of free carriers in the conduction band.…”
supporting
confidence: 82%
“…Ti 3d transition, suggesting that the raised conduction band minimum contributes to the increased gap for this transition as well. The Cr 3d band is expected to have minimal dispersion due to the localized nature of the dopants at low concentrations, 24 so it is reasonable to expect that the dopants will produce either a direct or nearly direct gap material.…”
mentioning
confidence: 99%
“…Downloaded to ] IP: Ni, Zn, Cr, Fe) octahedra isolate each other. The electron hopping between d 0 cations is impeded by the presence of d n cation in the BO 2 layer and this results in the reduction of bandwidth 29. Despite the VBM being raised by the emergence of d n states, band gaps of rocksalt-ordered A(in the visible region, both its valence and conduction band are now composed of Fe d states…”
mentioning
confidence: 93%
“…It is important because the physical properties of ordered compounds could be different of those of the random alloys. Chen et al, e.g., showed that the electronic structure of (SrTiO 3 ) 1−x (LaCrO 3 ) x alloy can be tuned by controlling the cation arrangement [13]. It is not simple to predict if an alloy would present ordered phases and, if so, which kind of order, since it depends, among other things, on the cationic sizes and charge differences, bond valence, and tolerance factor [14][15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%